Comparative evaluation of different bioformulations of PGPR cells on the enhancement of induced systemic resistance (ISR) in Rice P. oryzae pathosystem under upland condition - C.Sekar, Umashankari.J and (Current Botany, 2011)
The comparative evaluation of different bioformulations, viz.,vegetative cell application, co-inoculation and co-aggregates application of efficient PGPR cells viz., Pseudomonas fluorescens (PF-3) and Paenibacillus polymyxa (B-19), together with challenge inoculation of Pyricularia oryzae on the enhancement of induced systemic resistance (ISR) in Rice-Pyricularia oryzae pathosystem was studied under pot culture condition with rice cv.ASD-19. It was observed that the application of Pseudomonas fluorescens and Paenibacillus polymyxa, as co-aggregates, altered the biochemical and physiological parameters viz., reducing and non-reducing sugars, total phenol content and defense enzymes activities such as peroxidase (PO), polyphenol oxidase (PPO), of rice plant to a significant level followed by co-inoculation and vegetative cell application of PGPRÃ‚Â  cells. The application of PGPR cells, as co-aggregates, was found to augment the total phenol content and defense enzyme activities such as PO and PPO content of rice plant to a higher level whereas a reduction in reducing and non-reducing sugar level was recorded, which ultimately lead to a reduction of Pyricularia oryzae incidence in upland rice. It has been postulated that the EPS biosynthesis of PGPR cells during co-aggregation processes might act as elicitor for the enhancement of ISR in Rice-Pyricularia oryzae pathosystem whereas the vegetative cells and co-inoculation processes, without any involvement of EPS, responded poorly for the enhancement of ISR in the same pathosystem. <span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This is the first comprehensive report on the role of bacterial EPS, as a determinant of ISR, in Rice - Pyricularia oryzae pathosytem and it needs further elaborate research on the topic.